The correlation between renal functional reserve and serum uric acid and quality of life in chronic kidney disease stage I–III - Savytska, L.M. (KIDNEYS, 2021)
Background. In clinical practice the renal functional reserve can be an important tool to identify the early kidney functional damage, cure them and impact diseases prognosis. The aim of this article was to review the concept of renal functional reserve in its relation with serum uric acid level and the quality of life in chronic kidney disease stage I–III. Materials and methods. The study included twenty-two patients with chronic kidney disease stage I–III. We used the renal functional reserve test of Hozhenko A.I. adapted to ambulatory medical care services with measuring serum uric acid level before and after water-salt loading with 0.5% sodium chloride. We assessed the quality of life using the SF-36 questionnaire. Results. Functional renal reserve was preserved in 19 patients (87 %) and averaged 115 ± 54 %, decreased in 2 patients (9 %), average 5.7 ± 2.1 %, and was absent in 1 patient (4 %) and valued –41 %. The level of functional renal reserve correlated with serum uric acid level, measured an hour after the water-salt load (p = 0.60; p-level 0.018), and the average value of uric acid was determined over 4 years (p = 0.74; p-level 0.0015). The renal functional reserve related with the scales of physical functioning (p = 0.60; p-level 0.03), vital activity (p = 0.68; p-level 0.01) and mental health (p = 0.58; p-level 0.04) while examining health-related quality of life. Conclusions. Our findings indicate that serum uric acid levels should be controlled in patients with high renal functional reserve.